Tópicos matriciais e determinantes - Fonseca, Rondinelli Rocha da (2013)
In this paper we discuss some topics and determinants matrix and its application in high school. In particular, the Gram matrix in a linear transformation which can be applied, for example, to calculate the area of a triangle in terms of their sides and also Gramiano (Gram matrix determinant) for calculating the volume of a parallelepiped. Both can be applied in high school. In this work we tembém a generalization of the vector product and some of its properties involving determinants. Finally we show the identity of Lagrange.